2013
DOI: 10.5603/fm.2013.0043
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic variability of groin innervation

Abstract: (Folia Morphol 2013; 72, 3: 267-270)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 10 publications
(20 reference statements)
0
11
0
1
Order By: Relevance
“…13,14 Studies have shown that failure to demonstrate the nerves during the hernia repair is associated with postoperative groin pain which reported in the range of 6-30% in the literature. [13][14][15] Five of our patients had variations in the course of inguinal nerves.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…13,14 Studies have shown that failure to demonstrate the nerves during the hernia repair is associated with postoperative groin pain which reported in the range of 6-30% in the literature. [13][14][15] Five of our patients had variations in the course of inguinal nerves.…”
Section: Discussionmentioning
confidence: 87%
“…13 Bachul et al demonstrated an absent ilioinguinal nerve along with an atypical course of genital branch of genitofemoral nerve. 15 These variations should be kept in mind when hernia repair being carried out to avoid the postoperative paresthesia and chronic groin pain.…”
Section: Discussionmentioning
confidence: 99%
“…teres uteri, das durch den Leistenkanal verläuft. Nerven, die im Leistenkanal verlaufen, sind der N. ilioinguinalis und der R. genitalis des N. genitofemoralis, wobei die Verläufe vielfach eine anatomische Lagevariabilität haben [12,13]. Diese Nerven sind ausschließlich für die oberflächliche Hautsensitivität in der Leistenregion zuständig.…”
Section: Anatomie Des Leistenkanalsunclassified
“…The motor fibers of the ilioinguinal nerve have also been seen intermingling with the genital branch of the GFN that innervate the cremasteric muscles in some studies (Moosman and Oelrich, 1978; Rab et al, ; Liu et al, ). Finally, asymmetry of the inguinal nerve distributions was noted in many cadaveric studies (Akita et al, ; Rab et al, ; Liu et al, ; Bachul et al, ), thus contributing to the variability of the inguinal region.…”
Section: Introductionmentioning
confidence: 97%
“…However, studies have shown some anatomical variability in the course the genital branch of the GFN and its relationship to the ilioinguinal nerve in this region (Moosman and Oelrich, ; Lichtenstein et al, ; Akita et al, ; Rab et al, ; Liu et al, ; Bachul et al, ). Rab et al () suggested a classification system to define the distribution patterns of the genital branch of the GFN and ilioinguinal nerve into four types.…”
Section: Introductionmentioning
confidence: 99%